A research agenda for environmental economics - Ruth, Matthias (Elgar Research Agendas, 2020)
Contents: 1. The roads less traveled / Matthias Ruth, University of Alberta, Edmonton, Canada -- 2. Environmental economics is dead! Long live environmental economics! / Mark Sagoff, George Mason University, Fairfax, Virginia, USA -- 3. Conceptual and political foundations for examining the interaction between nature and economy / Malte Faber and Martin Frick, University of Heidelberg, Germany -- 4. Ends, means, and the economics of environment / Deepak Malghan, Indian Institute of Management, Bangalore, India -- 5. Ecosystems, legal systems, and governance: An institutional perspective / Lee P. Breckenridge, Northeastern University, Boston, Massachusetts, USA -- 6. Macroeconomics and the environment / Martin R. Sers and Peter A. Victor, York University, Canada -- 7. Contemporary economics and contradictions for climate maladies: Lessons from environmental macroeconomics / Dodo J. Thampapillai, National University of Singapore, Singapore, and Australian National University, Canberra, Australia, and Matthias Ruth, University of Alberta, Edmonton, Canada -- 8. Energy intensity: The roles of rebound, capital stocks, and trade / Astrid Kander, Lund University, Lund, Sweden, M. d. Mar Rubio Varas, Universidad Publica de Navarra, Pamplona, Spain, and David I. Stern, The Australian National University, Canberra, Australia -- 9. Place-based behavior and environmental policies / Eveline van Leeuwen, Wageningen University, Wageningen, The Netherlands -- 10. New ways of valuing ecosystem services: Big data, machine learning, and the value of urban green spaces / Christian Krekel, London School of Economics, London, England and Jens Kolbe, Technische Universität Berlin, Berlin, Germany -- 11. Are household borrowing constraints bad for the environment? Theory and cross-country evidence / Dana C. Andersen, University of Alberta, Edmonton, Canada -- 12. Manufacturing doubt: How firms exploit scientific uncertainty to shape regulation / Yann Bramoullé, Aix-Marseille University, Marseille, France and Centre national de la recherche scientifique, Paris, France, and Caroline Orset, Université Paris-Saclay, Paris, France -- 13. Solution design through a stakeholder process as a new perspective for environmental economics with illustrations from Indian case studies / René Kemp and Shyama V. Ramani, UNU-MERIT and ICIS, Maastricht University, Maastricht, The Netherlands -- 14. Optimizing the reversal of life: A coevolutionary response / Jalel Sager and Richard B. Norgaard, University of California Berkeley, Berkeley, California, USA -- Index.